Medicinal impact of microalgae collected from high rate algal ponds; phytochemical and pharmacological studies of microalgae and its application in medicated bandages. (July 2019) - Hussein, Rehab A.; Salama, Abeer A.A.; El Naggar, Mehrez E.; Ali, Gamila H.
Abstract: In the course of maximizing the utilization of natural resources, microalgal communities growing in high rate algal ponds are being investigated for possible pharmacological and medicinal values. An algal community predominated by Microcystis aeruginosa was phytochemically studied using Liquid chromatography with Photodiode array detector coupled with electron spary ionization mass spectroscopy (LC-DAD/ESI-MS). A pharmacological screening including antioxidant, anti-inflammatory, anti-diabetic and cytotoxic actions was conducted. The application of Microcystis aeruginosa predominant algal extract in formulating medicated bandages to aid healing of diabetic wounds was further evaluated. The phytochemical investigation of the algal extract led to the separation and identification of hydroxypheophytin-a, astaxanthin and phytoene in the algal extract which showed marked antioxidant and anti-inflammatory activities at 500 mg/kg dose level. At a dose of 200 and 400 mg/kg, it significantly diminished glucose levels in diabetic rats' sera in a dose-dependent manner. Marked decline in serum nitric oxide and catalase values was detected along with a significant increase in serum insulin, glucose transporter 2 and cluster of differentiation 4 levels. The obtained results indicated that the use of the algal based medicated bandages on wounds induced in diabetic rats showed progressive healing as compared to untreated rats. A considerable decrease in serum tumor necrosis factor-α accompanied by the increase in serum collagen-I was observed. The histopathological inspection of rats' skin ascertained the improvement in skin condition. Graphical abstract: Image 1